Moral Education of Children of Pre-School Age in the Light of the Achievements of Ukrainian Ethnopedagogics - Abramovych, Galyna; Sofiyan, Lyudmyla (Pedagogical Discourse, 2012)
The folk experience of moral education of children of pre-school age using the achievements of Ukrainian ethnopedagogics is generalized in the article. Historical aspect of development of moral education of children of pre-school age taking into account achievements in the questions of moral education of Ukrainian ethnopedagogics is analysed.